Model Pengukuran Tingkat Kepuasan Masyarakat Terhadap Penggunaan Jasa Transportasi Online di Wilayah Cirebon dengan Metode Fuzzy Servqual - Nursaka Putra; Ilwan Syafrinal; Marsani Asfi (Institut Teknologi Sepuluh Nopember, 2020)
Online transportation responds to people's needs in relation to public transport. Online transportation, which in this context is Grab and Go-Jek, is an alternative that is favored by many people, especially in the Cirebon area. This study aims to measure the level of service satisfaction received and future customer expectations of online transportation services. For our purpose, we use Fuzzy Service Quality method which is used to determine the variable customer needs that are not met by calculating the GAP between the services provided and the expectations of the customer as the Voice of Customer, where the data collection technique is carried out by distributing questionnaires. The results are Reliability rank 2 with a value of 0.100, Responsiveness rank 4 with a value of 0.86, Assurance rank 3 with a value of 0.090, Empathy rank 5 with a value of 0.040, Tangibles rank 1 with a value of 0.139. Based on these results, we suggest that an empathy-related policy-making concerning professionalism should not become an obstacle.